Outpatient Parenteral Antibiotic Treatment for Infective Endocarditis: A Prospective Cohort Study From the GAMES Cohort. (14th January 2019) - Pericà s, Juan M; Llopis, Jaume; González-Ramallo, Víctor; Goenaga, Miguel Á; Muñoz, Patricia; García-Leoni, M Eugenia; Fariñas, M Carmen; Pajarón, Marcos; Ambrosioni, Juan; Luque, Rafael; Goikoetxea, Josune; Oteo, José A; et al.
Abstract: Background: Outpatient parenteral antibiotic treatment (OPAT) has proven efficacious for treating infective endocarditis (IE). However, the 2001 Infectious Diseases Society of America (IDSA) criteria for OPAT in IE are very restrictive. We aimed to compare the outcomes of OPAT with those of hospital-based antibiotic treatment (HBAT). Methods: Retrospective analysis of data from a multicenter, prospective cohort study of 2000 consecutive IE patients in 25 Spanish hospitals (2008–2012) was performed. Results: A total of 429 patients (21.5%) received OPAT, and only 21.7% fulfilled IDSA criteria. Males accounted for 70.5%, median age was 68 years (interquartile range [IQR], 56–76), and 57% had native-valve IE. The most frequent causal microorganisms were viridans group streptococci (18.6%), Staphylococcus aureus (15.6%), and coagulase-negative staphylococci (14.5%). Median length of antibiotic treatment was 42 days (IQR, 32–54), and 44% of patients underwent cardiac surgery. One-year mortality was 8% (42% for HBAT; P < .001), 1.4% of patients relapsed, and 10.9% were readmitted during the first 3 months after discharge (no significant differences compared with HBAT). Charlson score (odds ratio [OR], 1.21; 95% confidence interval [CI], 1.04–1.42; P = .01) and cardiac surgery (OR, 0.24; 95% CI, .09–.63; P = .04) were associated with 1-year mortality, whereas aortic valve involvement (OR, 0.47; 95% CI, .22–.98; P = .007) was the only predictor of 1-year readmission. Failing to fulfill IDSA criteria was not a risk factor for mortality or readmission. Conclusions: OPAT provided excellent results despite the use of broader criteria than those recommended by IDSA. OPAT criteria should therefore be expanded. Abstract : The use of outpatient parenteral antibiotic treatment to treat infective endocarditis patients using less restrictive criteria than those proposed by the IDSA was efficacious and safe.